PENGARUH KREATIVITAS MENGAJAR GURU TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SMA N 1 MUARA PADANG BANYUASIN SUMATERA SELATAN - Tri Ani Oktaria; Riswan Jaenudin; Rusmin AR (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2017)
The research entitled “The Effect of Teacher Teaching Creativity on Students’ Learning Outcomes in Economics subjects at SMA N 1 Muara Padang”. The formulation of research problem was “whether there was influence of teacher teaching creativity to student learning outcomes one conomic subject in SMAN1 Muarapadang”.Population in this research was all of the teacher of economic subject and student of class X and XI in SMA N 1 Muara Padang. Sampling research used purposive sampling, so that all subject economic subject became samples and selected class XI IPS 1, XI IPS 2 and X IPA 2. Technique Collecting data used in this Study were observation, questionnaires, interviews and documentation. Technique of data observation analysis obtained from observation of teacher who taught before daily test, obtained average teacher teaching creativity equal to 79,01% into good category. Technique of questionnaire data analysis obtained average-equal to 68,92% into good category, while result of data analysis of documentation value of student daily average value equal to 84,85%. Hypothesis used parametric statistic that was simple regressi on test obtained Fcount ≥ Ftable or 33,22≥3,96. This showed that there wasinfluence of teacher teaching creativity to student learning outcomes one conomic subjects in SMA N 1 Muara Padang. It is recommended for further researchers to examine more than one school and use more than three teachers as the samples and describe other factors that influence the learning outcomes.